Manfaat Budaya Sekura dalam Peningkatan Perekonomian Masyarakat di Lampung Barat melalui Acara Festival Sekura Cakak Buah - Melia Pitriyani; Siti Hasanah HS; Rahmat Prayogi; Bambang Riadi (STIKes Ibnu Sina Ajibarang, 2024)
The famous dance parade activity in Lampung, especially West Lampung. This study will discuss the dance tradition which is usually called sekura. The purpose of this study is to examine information about the benefits of the sekura tradition for improving the economy of the people in West Lampung. This festival is an event to introduce the sekura tradition to the community, especially foreign tourists who may have never seen this event. This has a positive impact on increasing the income of the local community. The methods used in this study are literature studies and interviews. The results of this study are that the sekura tradition in West Lampung has the potential to improve the economy of the local community.